2010
DOI: 10.1073/pnas.1007610107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of eukaryotic initiation factor-2α promotes the extracellular survival of obligate intracellular parasite Toxoplasma gondii

Abstract: While seeking a new host cell, obligate intracellular parasites, such as the protozoan Toxoplasma gondii, must be able to endure the stress of an extracellular environment. The mechanisms Toxoplasma use to remain viable while deprived of a host cell are not understood. We have previously shown that phosphorylation of Toxoplasma eukaryotic initiation factor-2α (TgIF2α) is a conserved response to stress. Here we report the characterization of Toxoplasma harboring a point mutation (S71A) in TgIF2α that prevents p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 29 publications
(49 reference statements)
7
88
0
Order By: Relevance
“…In Toxoplasma gondii, TgeIF2␣ phosphorylation is important for maintaining the latency of the bradyzoite form in the mammalian host (8). Moreover, it has been reported that phosphorylation of eIF2␣ in Toxoplasma gondii is critical for the resistance of the parasite to external stress outside its host; inhibition of this phosphorylation significantly delays the development of acute toxoplasmosis in vivo (9). In Plasmodium, phosphorylation of PfeIF2␣ is essential for the development of the erythrocytic cycle (10), and nutritional stress-induced eIF2␣ phosphorylation in Trypanosoma cruzi regulates metacyclogenesis (11).…”
mentioning
confidence: 99%
“…In Toxoplasma gondii, TgeIF2␣ phosphorylation is important for maintaining the latency of the bradyzoite form in the mammalian host (8). Moreover, it has been reported that phosphorylation of eIF2␣ in Toxoplasma gondii is critical for the resistance of the parasite to external stress outside its host; inhibition of this phosphorylation significantly delays the development of acute toxoplasmosis in vivo (9). In Plasmodium, phosphorylation of PfeIF2␣ is essential for the development of the erythrocytic cycle (10), and nutritional stress-induced eIF2␣ phosphorylation in Trypanosoma cruzi regulates metacyclogenesis (11).…”
mentioning
confidence: 99%
“…Studies have shown that S71A-TgIF2␣ mutant parasites are ill-equipped to cope with the extracellular environment following egress from the host cell. Consequently, S71A-TgIF2␣ parasites suffer reduced viability in the extracellular environment and slowed replication following infection of a new host cell (61). Furthermore, parasites lacking the GCN2-like eIF2␣ kinase called TgIF2K-D fail to recover from extracellular stress as efficiently as the wild type, a defect that was also observed for the S71A-TgIF2␣ mutant (62).…”
Section: Translational Control During the Toxoplasma Lytic Cyclementioning
confidence: 80%
“…In contrast to Plasmodium, Toxoplasma tachyzoites harboring a point substitution at Ser71 to alanine (S71A) are viable (52,61). However, parasites deficient in stressinduced TgIF2␣ phosphorylation (S71A-TgIF2␣) showed a pronounced reduction in viability and slowed progression through the lytic cycle in the absence of exogenous cellular stress (61). Toxoplasma tachyzoites rapidly progress through a virus-like lytic cycle in any nucleated cell, which includes adherence and invasion of a host cell, multiple rounds of intracellular replication, and egress from the host cell (Fig.…”
Section: Translational Control During the Toxoplasma Lytic Cyclementioning
confidence: 99%
“…Furthermore other molecules, such as the calcium-dependent protein kinases (19) and abscisic acid (20), participate in host cell invasion pathways and are also central players in stress responses in plants. Indeed, it has been hypothesized that egress from the host cell is the largest stress in the life cycle of Toxoplasma and other intracellular pathogens, and activation of stress responses involved in invasion has been shown to be critical for Toxoplasma extracellular viability (25). Therefore, if the function of a stress response protein such as DJ-1 is compromised, parasites may not be able to efficiently attach and invade into the host cell.…”
Section: Discussionmentioning
confidence: 99%